1993
DOI: 10.1177/105256299301700101
|View full text |Cite
|
Sign up to set email alerts
|

Women's Experiences and Ways of Knowing: Implications for Teaching and Learning in the Organizational Behavior Classroom

Abstract: This article, based on the author's teaching experiences and relevant research on gender, explores the implications of women's ways of knowing for the organizational behavior classroom. The article traces historical, cultural, and developmental roots for the feelings of self-doubt, novelty, terror, and alienation that often accompany women into the management classroom. The article explores the implications for teaching organizational behavior effectively and suggests ways for creating a more equitable and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Zhang et al's (2013) study also offers evidence that if both men and women receive entrepreneurship education, men have a higher log-chance of entrepreneurial intentions than females. Some earlier studies have also found differences in learning styles between men and women (Gallos, 1993;Kaenzig et al, 2007;Varamäki et al, forthcoming). According to these studies, women are not as happy with group work or active-based pedagogies as men are.…”
Section: Development Of Entrepreneurial Intentionmentioning
confidence: 81%
See 1 more Smart Citation
“…Zhang et al's (2013) study also offers evidence that if both men and women receive entrepreneurship education, men have a higher log-chance of entrepreneurial intentions than females. Some earlier studies have also found differences in learning styles between men and women (Gallos, 1993;Kaenzig et al, 2007;Varamäki et al, forthcoming). According to these studies, women are not as happy with group work or active-based pedagogies as men are.…”
Section: Development Of Entrepreneurial Intentionmentioning
confidence: 81%
“…For example, women might react differently to pedagogical methods than males. As such, there might be differences in learning styles between men and women (Gallos, 1993). Also, the effectiveness and value of teambased pedagogical exercises for women students has been called into question, because women seem to be less happy with team-based exercises in business classes (e.g.…”
Section: Intentions Decrease During Studiesmentioning
confidence: 99%
“…Finally, the literature on gender bias in the college classroom (Gallos, 1993;Maher, 1985;Sadker and Sadker, 1990) and research regarding how women learn (Beer and Darkenwald, 1989;Belenky, Clinchy, Goldberger, and Tarule, 1986;Luttrell, 1989) informs the HRD practitioner that in academic settings, the climate is often perceived as "chilly" for women. In addition Tisdell (1993aTisdell ( , 1993b suggests that the adult education environment often perpetuates power relationships based on gender, race, class, and age, thus reinforcing the white, male-dominated structure that permeates society.…”
Section: Trainingmentioning
confidence: 99%
“…Especially at exam time, both students and faculty may find themselves under the influence of a &dquo;banking&dquo; metaphor of education, which assumes that the goal of evaluation is to assess the extent to which students have &dquo;filled up their heads&dquo; with preselected knowledge and skills (Friere, 1971;Gallos, 1993a;Hazen, 1987Hazen, -1988. In its most primitive form, this metaphor generates multiple choice tests that keep students locked into memory exercises.…”
mentioning
confidence: 99%